2016
DOI: 10.1021/acs.cgd.5b01672
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Solid-State Hydration/Dehydration of Paroxetine HBr Hemihydrate: Structural and Thermochemical Studies

Abstract: For active pharmaceutical ingredients (API) in the solid state, the occurrence of hydration/dehydration phase transitions may have implications upon the efficiency of the pharmaceutical product, once they are often accompanied by changes of physicochemical properties. Thus, it is important for pharmaceutical research and development to investigate these mechanisms based on the crystal structures of the API. In this work, beyond the structural characterization of a new salt of the antidepressant drug Paroxetine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…It was revealed that both form I and its dehydrate are isostructural with the corresponding paroxetine hydrobromide forms. 3 Comparison of the structures gives an explanation of the different stabilities and transformation kinetics observed. Form II contains solvent pockets separated by easy-to-open gates, and consequently it behaves as a channel hydrate.…”
Section: -8mentioning
confidence: 99%
See 2 more Smart Citations
“…It was revealed that both form I and its dehydrate are isostructural with the corresponding paroxetine hydrobromide forms. 3 Comparison of the structures gives an explanation of the different stabilities and transformation kinetics observed. Form II contains solvent pockets separated by easy-to-open gates, and consequently it behaves as a channel hydrate.…”
Section: -8mentioning
confidence: 99%
“…2,3 In some cases it can be preferable to synthesize a cocrystalline compound instead of a salt, for example based on the poor predictability of salt structures in respect of their chemical and stoichiometric composition. To select suitable compounds for targeted cocrystal growth, the pK a -rule is a helpful tool.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the presence of water molecules, the hydrogen bonding network in the crystal lattice is changed in comparison to the respective anhydrous forms, and therefore, it affects the pharmacokinetic and physicochemical properties of a solid, such as its solubility, dissolution rate, stability and bioavailability. For only a few examples of the above-mentioned difficulties, we can refer to the recent papers on ciprofloxacin, 6 sildenafil, 7 guanosine, 8 paroxetine hydrochloride and hydrobromide, 9,10 ortoic acid 11 or (+)-catechin. 5 A full description of the dehydration and rehydration processes and their influence on the API structures is still challenging because of the number of issues that must be addressed, with only several of them being the following: (i) the precise water content in the crystal lattice, (ii) how water molecules are located in the crystal lattice, (iii) whether a specific API is a hygroscopic anhydrate or a nonstoichiometric hydrate, (iv) how water molecules interact with an API molecule, (v) how dehydration influences the API structure, and (vi) the dynamics of the process.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding and accounting for the role of water in the formation and stability of molecular crystals of small organic moieties and natural products is challenging from both the intellectual and experimental points of view. The challenge is met on each stage of crystal formation starting from preorganization, followed by the growing of regular forms with water content, and finally the dehydration process, which is often related to the collapse of the subtle structure . This problem affects a significant population of crystals.…”
Section: Introductionmentioning
confidence: 99%